2017
DOI: 10.1007/s11060-016-2365-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ki67, HMGA1, MDM2, and RB expression in nonfunctioning pituitary adenomas

Abstract: Nonfunctioning pituitary adenomas (NFPAs) are the most prevalent type of pituitary macro-adenoma. Clarifying the relationship between NFPA markers and disease progression or recurrence could provide a basis for administration of adjuvant treatments. The present study examined the expression levels of high-mobility group (HMG)A1, Ki-67, mouse double minute 2 homolog (MDM2), and retinoblastoma (RB)with respect to NFPA recurrence. Immunohistochemistry was carried out using antibodies to Ki-67, MDM2, HMGA-1, and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…other factors that influence the proliferation of pituitary adenomas, such as angiogenesis, growth factors, oncogenes, apoptosis, tumor suppressor genes, and hormone receptors, have been shown to be predictive factors (15,(19)(20)(21). In this study, our results indicated that age, tumor size, cavernous sinus invasion, sphenoid sinus invasion, and surgery extension were the significant risk factors that were used to build the nomogram.…”
Section: A B Cmentioning
confidence: 62%
See 1 more Smart Citation
“…other factors that influence the proliferation of pituitary adenomas, such as angiogenesis, growth factors, oncogenes, apoptosis, tumor suppressor genes, and hormone receptors, have been shown to be predictive factors (15,(19)(20)(21). In this study, our results indicated that age, tumor size, cavernous sinus invasion, sphenoid sinus invasion, and surgery extension were the significant risk factors that were used to build the nomogram.…”
Section: A B Cmentioning
confidence: 62%
“…Another study indicated that a Ki-67 labeling index (LI) above 2.2% should attract more attention and require shorter intervals of follow-up with early adjuvant therapy and magnetic resonance imaging (MRI) scans (14). In contrast, Yao et al showed no statistical significance of the Ki-67 LI in primary (n=20) or recurrent tumors (n=15) (15). Recently, Cheng et al demonstrated a predictive model for NFPA that could facilitate prognostic evaluation and guide early interventions (9).…”
Section: Original Articlementioning
confidence: 99%
“…Overexpression of MDM2 has been reported in many malignant tumors (Momand et al 1998). In addition, MDM2 expression has been reported to be correlated with progression of tumors, such as nonfunctioning pituitary adenoma (Yao et al 2017). Increased MDM2 expression was more frequently detected in seminoma and embryonal carcinoma than intratubular germ cell neoplasia (Datta et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…gene of p53, indicating that MDM2 may be a functional factor in pituitary adenoma [9]. Furthermore, Yao X et al found that MDM2 may be a biomarker and potential drug target for pituitary adenoma treatment [10]. However, the mechanism of MDM2 in pituitary adenoma has not been studied thoroughly and clearly.…”
Section: Co-immunoprecipitation (Co-ip) Assaymentioning
confidence: 99%